Self-assembly modified-mushroom nanocomposite for rapid removal of hexavalent chromium from aqueous solution with bubbling fluidized bed - Xu, Fei (Nature Publishing Group, 2016)
A self-assembled modified Pleurotus Cornucopiae material (SMPM) combined with improved Intermittent Bubbling Fluidized Bed (IBFB) was investigated to remove the hexavalent chromium ions in aqueous solution. After the modification, the powder-like raw material gradually self-assembled together to SMPM, which had crinkly porous structure, improved the Cr-accommodation ability in a sound manner. Optimized by Taguchi method, Cr(VI) removal efficiency was up to 75.91% and 48.01% for 100 mg/L and 500 mg/L initial concentration of Cr(VI), respectively. Results indicated that the metal removal was dependent on dosage of adsorbent, particle diameter and treatment time. The experimental data obtained from the biosorption process was successfully correlated with Freundlich isotherm model. Thermodynamic study indicated the endothermic nature of the process. The results confirmed that self-assembly modified Pleurotus Cornucopiae material could be applied for the removal of heavy metal from wastewater in continuous fluidized bed process.